Pelatihan Penggunaan Aplikasi LMS Kelas Online untuk Staf Admin LKP Zahra Computer - Siti Agrippina Alodia Yusuf; Nani Sulistianingsih (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
Participating in online training will help to continue the present capacity-building process. To meet these demands, training service providers such as LKP Zahra Computer have developed a Learning Management System (LMS) that allows for more flexible training. LMS administration for Admin Staff is one of the reasons that becomes a barrier for LKP, especially when it comes to publishing new classes, adding questions to the system, and upgrading classes if there are modifications that are needed. The initial stage of this training is an interview with the administrative staff to identify potential impediments. Following that, the second level, which included online class LMS management training, was completed. And at last, the Admin Staff constructed a mock class to evaluate their understanding of the Online Class LMS management.